Modern Albania : From Dictatorship to Democracy in Europe - Abrahams, Fred (Book collections on Project MUSE., 2015)
""The canon on modern Albanian political history in English is small but Fred Abraham's book is now a large contribution to it. Excellent and above all readable and pacy, anyone interested in contemporary Albanian and Balkan history should be grateful that he has committed his deep knowledge about the country, and above all its travails in the 1990s, to paper.""--Tim Judah, author of Kosovo: War and Revenge.